Biodiversity of a wreck from the Belgian Continental Shelf: monitoring using scientific diving. Preliminary results. - Massin, C.; Norro, A.; Mallefet, J. (Bulletin de l'Institut Royal des Sciences Naturelles de Belgique (Biologie), 2002)
Scientific diving from aboard the r/v Belgica has been employed to carry out a preliminary study of the macrofauna living on a wreck (the Birkenfels) located on the Belgian Continental Shelf (BCS). The study revealed an extremely rich sessile and slow moving fauna (at least 40 species), 3 jellyfish species and 8 fish species. The presence of at least 51 species represents a biodiversity of macrofauna on the wreck that is much higher than that found in nearly all known surrounding soft bottom communities belonging to the BCS. The covering of large parts of the wreck is represented by three species: Sarsia eximia (Hydrozoa) and Jassa herdmanni (Crustacea) associated with Tubularia indivisa (Hydrozoa). It should also be pointed out that 53 % of the species identified in this study are species not included as members of the Belgian marine fauna in a recent list dealing with offshore fauna. Moreover, some. such as Sarsia eximia or Epithonium clathratulum, previously thought to be rare, have been found in large numbers. Furthermore, Diadumene cincta and Caprella tuberculata are new species for the Belgian marine fauna.
Ant'Phipoda Literature database